Ecologies, Economies, and Communities: The Alternative of Community Economic Development - Melchin, Kenneth R (Journal of Dharma, 1993)
The subtitle of this issue, "Ecoharmony vs. Economic Equity" suggests a fundamental conflict between environment and economy. To be sure, there are analyses supporting this view. Countries of the North often see the threat to the world’s eco-system -as requiring environmental regulations to implement costly technologies. Such technologies are promoted as the route towards reducing hazardous emissions, controlling the consumption of non-renewable resources, and curbing the destruction of the eco-systems that support life. But these costly measures are regarded with suspicion by the nations of the South. How can countries which are now failing to provide food, clothing. housing, health care, and education to their peoples accept environmentat regulations which add enormous costs to their development efforts? Must the poorer countries choose between development and environment? Some argue that these technologies should be provided by the North. Then how should the North allocate scarce resources for aid; to environment or to development?